S70 Collagen deposition by fibroblasts could contribute to disease progression in Lymphangioleiomyomatosis. (11th November 2022) - Clements, D; Babaei-Jadidi, R; Miller, S; Leeming, D-J; Johnson, SR
Abstract : Lymphangioleiomyomatosis (LAM) is a rare, female-specific cystic lung disease in which destruction of the lung parenchyma is driven by lesions containing TSC2 -/- LAM cells and recruited stromal LAM associated fibroblasts (LAFs). LAM patients can be treated with rapamycin to stabilise lung function, but some patients continue to decline, and additional therapies are needed for these patients. We hypothesised that extracellular matrix (ECM) deposited by LAFs within lesions could affect LAM cell behaviour and promote disease progression. We aimed to quantify ECM deposition in LAM, investigate its association with disease severity and study the effect of LAF deposited matrix on LAM cell behaviour in vitro. Methods: Collagen neoepitopes were measured in sera from 96 LAM patients and 22 controls using Nordic Bioscience assays. Collagen deposition in paraffin sections of LAM lung tissue was assayed by picrosirius red (PSR) staining and immunohistochemistry from 19 lung samples with linked clinical data. In vitro assays were performed on TSC2 -/- cells grown on cell-free LAF-derived ECM. Results: Serum markers of collagen, but not elastin turnover tended to be greater in women with LAM than controls (C6M, p=0.057). Quantification of PSR staining revealed trends toward ECM accumulation with increasing disease duration (r=0.62, p=0.060) and reducing DLCO (r=-0.55, p=0.057). LAF-derived ECM increased proliferation (p<0.0001) and reduced the anti-proliferative effect of rapamycin in TSC2 -/- cells (p=0.0004) in vitro . Conclusion: Collagen deposition can be observed in LAM lesions. LAF-derived ECM enhances TSC2 -/- cell proliferation in vitro and may contribute to disease progression by providing a pro-proliferative microenvironment for LAM cells in vivo . This may reduce response to rapamycin in some patients. These data support the investigation of anti-fibrotic therapies for LAM patients who respond poorly to rapamycin.